The Abuse of Right Principle in Japan and Germany - Droell, Felix (Teisė, 2024)
The article “The abuse of right principle between legal certainty and case-by-case justice deals with the application practice of the abuse of rights principle in Germany and Japan. As an instrument for resolving tensions between written law and the cultural and moral ideas of Japanese judges, the concept was imported to Japan in the 19th century in the course of the westernisation of the legal system. In the beginning, German and Japanese application practices were naturally very similar, but as time and historical development progressed, the two application regimes increasingly diverged. The Japanese judiciary has retained the free and little-controlled application practice of the 19th century, while the German judiciary today controls the concept much more tightly. In practice, this means that the Japanese Supreme Court does not give the lower courts any formal guidelines on application, but rather seeks to prevent grossly arbitrary applications by classifying possible arguments. The German judiciary, on the other hand, developed a complex structure of so-called case groups. Case grouping means that arguments are not classified as in Japan, but rather the actual factual constellations are conclusively determined as admissible or inadmissible. Thus, after approx. 120 years of independent development in Japan and Germany, there are considerable differences between the application practice of the prohibition of abuse of rights, despite the same starting point. The reasons for these differences are multifaceted in nature; within the framework of this paper, it was primarily possible to identify historical factors in the form of experience with arbitrary justice, cultural influences in the form of community orientation in Japan and institutional reasons in the form of court organisation.